2014
DOI: 10.3747/co.21.1903
|View full text |Cite
|
Sign up to set email alerts
|

One Compared with Two Cycles of Mitomycin C in Chemoradiotherapy for Anal Cancer: Analysis of Outcomes and Toxicity

Abstract: (1) Background: Concurrent chemoradiation with fluorouracil (5fu) and mitomycin C (mmc) is standard treatment for anal canal carcinoma (acc). The current protocol in Alberta is administration of 5fu and mmc during weeks 1 and 5 of radiation. However, administration of the second bolus of mmc has been based largely on centre preference. Given limited published data on outcomes with different mmc regimens, our objective was to compare the efficacy and toxicity of 1 compared with 2 cycles of mmc in acc treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
0
7
1
1
Order By: Relevance
“…A recently published retrospective study found no difference in 5-year DFS or OS between patients receiving one or two doses of MMC. On multivariate analysis, two cycles of MMC was the factor most strongly associated with grade 3þ skin toxicity (hazard ratio: 4.76; p < .001) and grade 3þ leukopenia (hazard ratio: 4.82; p < .01), which were reported in 72.8% and 45.7% of cases (73% and 43% in our series) [27]. It remains so far unclear whether the second dose of MMC improves efficacy, or merely increases toxicity.…”
Section: Discussionmentioning
confidence: 52%
“…A recently published retrospective study found no difference in 5-year DFS or OS between patients receiving one or two doses of MMC. On multivariate analysis, two cycles of MMC was the factor most strongly associated with grade 3þ skin toxicity (hazard ratio: 4.76; p < .001) and grade 3þ leukopenia (hazard ratio: 4.82; p < .01), which were reported in 72.8% and 45.7% of cases (73% and 43% in our series) [27]. It remains so far unclear whether the second dose of MMC improves efficacy, or merely increases toxicity.…”
Section: Discussionmentioning
confidence: 52%
“…Where disease‐free survival was reported, the outcome was defined in 20 studies, using nine different definitions (Table ). The most commonly used definition (local, regional or distant failure, second primary or death from any cause) was used in five studies . Four of these studies are from the same research organization (Radiation Therapy and Oncology Group) including two papers reporting short‐ and long‐term results of the same study .…”
Section: Resultsmentioning
confidence: 99%
“…Three-year OS, DFS and CFS Kaplan Meier estimates were also similar. A recent retrospective study by our group suggests reduction of grade 3+ hematological and skin toxicities with 1 MMC cycle versus 2 cycles in ACC treatment, without compromise to OS, CFS and DFS [ 24 ]. Potential differences in acute toxicities secondary to different chemotherapy regimens may have been mitigated by radiotherapy technique.…”
Section: Discussionmentioning
confidence: 99%